Thermokinetic and Structural Shape Memory Effect Characteristics of Novel Quaternary CuAlNiCr HTSMA - Karaduman, Oktay; Özkul, İskender; İstek, Gökhan; Canbay, Canan Aksu (Soner ÖZGEN, 2024)
CuAlNi shape memory alloys (SMAs) are one of the most prominent Cu-based SMAs mainly due to their shape memory properties at high temperatures. Therefore, they are interested in high temperature SMA applications. Their good thermal stability but brittleness originated from their coarse grain size are their other pros and cons. In this study, the low-cost quaternary CuAlNiCr high-temperature SMA (HTSMA) with a new unprecedented chemical composition including trace amount of chromium element was fabricated by arc melting technique. After arc melting process, traditional homogenization of small alloy samples in the high ?-phase temperature region and quenching them in iced-brine water were proceeded. To characterize the shape memory effect property of the alloy, differential calorimetry and microstructural X-ray diffraction (XRD) tests were carried out. The cyclic DSC (differential scanning calorimetry) tests carried out at various heating/cooling rates showed the splendid endothermic and exothermic peaks of reversible martensitic phase transformations in the temperature range between around 150-220 °C, thence the produced alloy is qualified as a high-temperature SMA. Using DSC peak analysis data, the finish and start temperatures of every martensitic phase transition, hysteresis gap, plus some other important thermodynamic parameters' values were also determined. Among them, the high enthalpy change amounts occurred during the transformations implied the good shape memory effect feature of the alloy. A DTA (differential thermal calorimetry) test taken at only one heating/cooling rate revealed both the reversible martensitic transformation peaks and the other phase transition peaks at higher temperatures. The consecutive phase transition step peaks of ?'1? B1(L21)?B2?A2 on the heating-part of the DTA thermogram curve of the alloy were observed as similar to those seen in the other Cu-based shape memory alloys. Furthermore, at room temperature, the presence and types of the martensite phases formed in the alloy were revealed by the XRD pattern of the alloy obtained by using CuK? radiation. The results showed that the novel CuAlNiCr high-temperature SMA can be useful in the high-temperature SMA applications.

CuAlNi şekil hafızalı alaşımlar (ŞHA'lar), esas olarak yüksek sıcaklıklardaki şekil hafızalı özelliklerinden dolayı en öne çıkan Cu-bazlı ŞHA'lardandır. Bu ŞHA'lara bu nedenle yüksek sıcaklık ŞHA uygulamalarında ilgi duyulmaktadır. İyi termal kararlılıkları ancak iri tane boyutlarından kaynaklanan kırılganlıkları diğer artıları ve eksileridir. Bu çalışmada, eser miktarda krom elementi içeren benzersiz bir kimyasal bileşime sahip dörtlü CuAlNiCr yüksek sıcaklık ŞHA (YSŞHA), ark eritme tekniği ile üretildi. Ark eritme işleminden sonra, küçük alaşım numunelerinin yüksek ? fazı sıcaklık bölgesinde geleneksel homojenleştirilip tuzlu buzlu suda hızlıca soğutuldu. Alaşımın şekil hafıza etkisi özelliğini karakterize etmek için diferansiyel kalorimetri ve mikroyapısal X-ışını kırınımı (XRD) testleri gerçekleştirildi. Farklı ısıtma/soğutma hızlarında gerçekleştirilen diferansiyel taramalı kalorimetri (DSC) testleri, yaklaşık 150-220 °C arasındaki sıcaklık aralığında tersinir martensitik faz dönüşümlerinin olağanüstü ekzotermik ve endotermik piklerini gösterdi; bundan dolayı üretilen alaşım bir yüksek sıcaklık ŞHA olarak sınıflandırıldı. DSC pik analizi verileri kullanılarak her bir martensitik faz dönüşümünün başlangıç ve bitiş sıcaklıkları, histeresiz aralığı ve diğer bazı önemli termodinamik parametreleri belirlendi. Bunlar arasında, dönüşümler sırasında meydana gelen yüksek entalpi değişim miktarları, alaşımın iyi şekil hafıza etkisi özelliğine sahip olduğuna işaret etmiştir. Tek bir ısıtma/soğutma hızında daha yüksek sıcaklıklara kadar çıkılarak yapılan diferansiyel termal kalorimetri (DTA) testi, hem tersinir martensitik dönüşüm piklerini yine ve hem de diğer faz geçiş piklerinin oluştuğunu gösterdi. Alaşımın DTA eğrisinin ısınma kısmında ?'1?B1(L21)?B2?A2 ardışık faz geçiş adımı pikleri diğer Cu bazlı şekil hafızalı alaşımlarda görülenlere benzer şekilde gözlendi. Ayrıca oda sıcaklığında alaşımda oluşan martensit fazların varlığı, alaşımın CuK? radyasyonu kullanılarak elde edilen XRD deseni ile ortaya çıkarılmıştır. Sonuçlar, yeni CuAlNiCr yüksek sıcaklık ŞHA'sının yüksek sıcaklık ŞHA uygulamalarında faydalı olabileceğini gösterdi.
Termodinamik ve Yapısal Şekil Hafıza Etkisinin Dörtlü CuAlNiCr YSŞHA Karakteristikleri
Keywords: Material Physics; Malzeme Fiziği; Thermodynamics and Statistical Physics; Termodinamik ve İstatistiksel Fizik